THE EFFECTIVENESS OF IMPLEMENTATION RESPONSIBILITIES FOR LOCAL GOVERNMENT BUDGET REGENCY/CITY IN THE NORTH MALUKU PROVINCE - SANGDJI, NASER; RUMKEL, NAM; HAKIM, ABDUL AZIZ (Sekolah Tinggi Ilmu Hukum Awang Long, 2019)
The purpose of this study was to analyze the effectiveness of implementation responsibilities for Local Government Budget regency/budget in the North Maluku Province, and the obstacles factor in its responsibilities. The type of research used is empirical normative legal research (applied) to examine the factual implementation or implementation of each particular legal event. The study aims to ascertain whether the results of the application are in accordance with the provisions of the Statutory Regulations. This empirical normative law research consists of 2 stages. Phase I study of normative law (legislation) Phase II study of empirical law in the form of implementation of the legal event. This study uses primary data and secondary data collected through interviews and observations. The collected data is then analyzed qualitatively. The results showed that the Mechanism of Responsibility for the Implementation of the Regency/City Regional Revenue and Expenditure Budget in the Government of North Maluku Province has fulfilled its obligations in preparing financial reports as regulated in Articles 294 and 295 of the Regulations. Minister of Home Affairs No. 13 Year 2007 concerning guidelines for managing Regional Finances. In this case the Regency/City in the North Maluku Provincial Government has implemented a digital-based accountability system that is in accordance with government accounting standards including SIMDA (Regional Financial Management Information System) E-Monev (Electronic Monitoring Evaluation) and Simolek (Electronic Financial Monitoring System). However, in its implementation there is often a delay in inputting overall accountability data, this is due to the slow collection of reports from each field, which occurs because of the non-functioning mechanism of the roles and duties of each employee. While the inhibiting factor is the delay in the accountability report from each field, it is not carried out in accordance with their respective tasks and functions, the lack of mental integrity and moral responsibility of employees, and the Regency/City Government does not submit Local Regulations and Regional Regulations after being evaluated by the Governor.